Breast Hypertrophy: A Real Pain in the Back. Issue 3 (21st November 2022) - Lessard, Lucie; Papanastasiou, Constantine; Fortin, Maryse; Ouellet, Jean A.
Abstract : Background: Bilateral breast hypertrophy comes with signs and symptoms ranging from mild to debilitating. Bilateral breast reduction (BBR) is one of the most frequently performed plastic surgery procedures, and its effects on parameters such as spinal balance, paraspinal muscle function, and physical performance have not been thoroughly evaluated. The objective of this study was to evaluate the effects of BBR using advanced spine imaging modalities, and pain resolution. Methods: A prospective, observational, cohort study was carried out at the McGill University Health Centre. The following measures were recorded preoperatively and postoperatively for each patient: patient questionnaires (BREAST-Q and Pain), magnetic resonance imaging, and EOS low-radiation spinal scan. Results: Significant postoperative pain reduction was recorded, and there was up to 148% improvement in physical tests. Improvement in all questionnaire and BREAST-Q categories was documented. Preoperative and postoperative magnetic resonance imaging did demonstrate a statistically significant absence of permanent anatomical skeletal sequelae. Postoperative improvement in thoracic kyphosis was documented. Conclusions: Quality-of-life scores are uniformly improved following BBR. Key findings following BBR include significant pain reduction and no evidence of spinal skeletal change. This is a finding of major importance in view of the practice of many insurance companies/third-party payer and health care systems that use the Schnur scale. The Schnur scale associates a weight for resection with body size that is not directly predictive of pain relief. This may indicate the need for more precise or different guidelines based on these quantitative findings. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.